2015
DOI: 10.3892/ijo.2015.3314
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells pulsed with tumor cells killed by high hydrostatic pressure induce strong immune responses and display therapeutic effects both in murine TC-1 and TRAMP-C2 tumors when combined with docetaxel chemotherapy

Abstract: High hydrostatic pressure (HHP) has been shown to induce immunogenic cell death of cancer cells, facilitating their uptake by dendritic cells (DC) and subsequent presentation of tumor antigens. In the present study, we demonstrated immunogenicity of the HHP-treated tumor cells in mice. HHP was able to induce immunogenic cell death of both TC-1 and TRAMP-C2 tumor cells, representing murine models for human papilloma virus-associated tumors and prostate cancer, respectively. HHP-treated cells induced stronger im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…In this regimen, DC-based vaccines were administered after the tumor challenge at regular intervals between docetaxel administrations. The tumor inhibitory effect of both immunogenic and weakly immunogenic models resulted in more effective suppression of growth, when compared with the untreated tumor-bearing animals [138]. A similar outcome was reported when the DC-based vaccines pulsed with HHP-treated tumor cells was combined with the chemotherapeutic cyclophosphamide [140].…”
Section: High Hydrostatic Pressuresupporting
confidence: 55%
See 2 more Smart Citations
“…In this regimen, DC-based vaccines were administered after the tumor challenge at regular intervals between docetaxel administrations. The tumor inhibitory effect of both immunogenic and weakly immunogenic models resulted in more effective suppression of growth, when compared with the untreated tumor-bearing animals [138]. A similar outcome was reported when the DC-based vaccines pulsed with HHP-treated tumor cells was combined with the chemotherapeutic cyclophosphamide [140].…”
Section: High Hydrostatic Pressuresupporting
confidence: 55%
“…Moreover, DCs that were loaded with HHP-treated tumor cells exhibited an upregulation of maturation markers, chemotactic migration, and the release of pro-inflammatory interleukins when compared to unloaded DCs. In addition, HHP-treated tumor lysate loaded-DCs were able to activate tumor-specific T cells while also downregulating the number of Treg [137][138][139][140].…”
Section: High Hydrostatic Pressurementioning
confidence: 98%
See 1 more Smart Citation
“…Spisek and colleagues also demonstrated that human ovarian and prostate tumor cells can be rendered immunogenic by HHP‐treatment and that DCs pulsed with HHP‐killed tumor cells induced tumor‐specific T cells . Combination of HHP‐vaccines with CT was efficient in inducing strong anti‐tumor immune responses . We observed in the murine B16 melanoma model that autologous HHP‐vaccine acts synergistically with RT to retard tumor growth (C. Seitz et al, unpublished data).…”
Section: Immunological Basis For Design Of Multimodal Radio‐immunothementioning
confidence: 71%
“…161 Combination of HHP-vaccines with CT was efficient in inducing strong anti-tumor immune responses. 162 We observed in the murine B16 melanoma model that autologous HHP-vaccine acts synergistically with RT to retard tumor growth (C. Seitz et al, unpublished data). HHP treatment of selected human cancer cell lines leads to degradation of tumor antigens.…”
Section: Combination Of Rt With Vaccination-high Hydrostatic Pressumentioning
confidence: 92%